Epistemology and Pedagogy: Knowledge, Comprehension, and Learning in Education Re-thought a Systematic Literature Review - Rivan Fatwa Aulia; Miftahul Janah; Siti Masturoh; Siti Anidapriyani; Mufidah Mufidah; Nur Cahya (Cahaya Smart Nusantara, 2026)
This research explores the interdependence of epistemology, pedagogy, and learning theory in modern-day educational reform through a systematic literature review. Reacting to rising criticisms of traditional educational frameworks that view knowledge as pre-existing and transferable, this paper highlights a move towards redefining knowledge as contextual, constructed, and socially mediated. The published peer-reviewed articles related to epistemological orientations, pedagogical practices, and learning processes are reviewed and published during the period 2019-2025, with a special focus on the constructivist and progressive approaches. As the results indicate, epistemological beliefs play a critical role in shaping pedagogy; the constructivist, pragmatic, and critical epistemologies are closely related to the learner-centered instruction model and support and encourage meaning-making, inquiry, and dialogue. On the other hand, classic epistemological approaches have been associated with supporting the teacher-centered pedagogy and surface learning outcomes. Also, the alignment of teachers’ epistemological beliefs is highlighted in the review as a mediating factor in curriculum design and instruction choice. In sum, the research argues that successful and significant educational change requires consistency of assumptions on epistemology, pedagogical strategies, and learning theories. The coordination between these three areas is not optional for the creation of profound knowledge, self-directed learning in the students, and long-lasting learning in the twenty-first-century learning environment.